Spain : Financial Sector Reform-Fourth Progress Report. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses findings of Fourth Progress Report on Spain's financial sector reform. Implementation of Spain's financial sector program remains on track. Essentially all measures specified in the program have now been implemented, as envisaged under its front-loaded timetable. Capital-augmentation measures arising from last year's stress test are now complete, SAREB has almost concluded its organizational development and is now accelerating the liquidation of its assets, and key reforms of Spain's financial sector framework have been adopted or put in train. Despite recent improvements, important risks remain, including those associated with the ongoing macroeconomic adjustment.